Pengaruh Likuiditas, Profitabilitas, Leverage, Ukuran Perusahaan, Audit Quality, Dan Opinion Shopping Terhadap Opini Audit Going Concern - Zahra, Lathifah; Wijayanti, Dwi Marlina (ACE: Accounting Research Journal, 2025)
A going concern audit opinion is an auditor's assessment that indicates that a company cannot maintain its business. This assessment has the effect of losing public trust in the company's image. The aim of this research is to analyze and provide empirical evidence regarding the influence of liquidity, profitability, leverage, company size, audit quality, and opinion shopping on going concern audit opinions in various industrial sector companies listed on the Indonesia Stock Exchange in 2017-2021. This research uses a purposive sampling technique with a sample size of 24 companies, with logistic regression analysis using EViews 12. The results of this research show that the liquidity and profitability variables have a negative effect on the acceptance of going concern audit opinions. Meanwhile, the variables leverage, company size, audit quality, and opinion shopping have no effect on receiving going concern audit opinions. The results of this research can be a reference for plans and policies in the company so that conditions remain stable for the sustainability of the company